The Effect of Peer Group Education on Anxiety of Patients with Multiple Sclerosis - Ali Dehghani; Sima Mohammadkhan Kermanshahi; Robabeh Memarian; Rasol Baharlou (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Multiple Sclerosis (MS) is one of the most common chronic diseases of the central nervous system which causes mental disorders including anxiety in patients. Since the peer group can better communicate with their counterparts and encourage them to choose appropriate healthy behaviors, this study was designed to examine the impact of peer educational program on anxiety of multiple sclerosis patients. Methods: This was a quasi-experimental study conducted in year 2011 in MS Society of Iran (Tehran). A convenient sample of 110 patients with MS was divided randomly into two equal groups (experimental and control). After preparing peer teachers, they held six training sessions for experimental group during six weeks. DASS-21 questionnaire was used to measure anxiety which was completed by both groups before and 4 months after the test. Data was analyzed using chi2, paired t, and independent t tests. Results: The findings of independent t test did not show any significant difference between anxiety scores of experimental and control group before intervention while a statistically significant difference was observed after intervention between the scores of two groups (p=.032). Paired t test showed a statistically significant difference in anxiety level in experimental group after intervention (p=.002), whereas the same test showed no statistically significant difference in control groups (p =.659). Conclusion: Peer group educational program reduced anxiety in patients suffering from MS. Hence the conduction of this program is recommended as an effective, affordable, and effective teaching method which did not require any special equipment.